Analisis Efektivitas Implementasi Model Project-based Learning Dalam Pelajaran Instalasi Penerangan Listrik - Saputri, Anatasa Alda; Usmeldi, Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This study aims to determine the effectiveness of the Project-based Learning model and student learning outcomes after implementing learning using the pjbl model in the Electrical Lighting Installation subject class XII TITL at SMK Muhammadiyah 1 Padang. Student learning outcomes are still low which is caused by learning factors that are still teacher-centered, thus affecting student learning outcomes in the cognitive and attitudinal domains. Therefore, it is necessary to apply a project-based learning model to find out how effective this learning model is on student learning outcomes. This research uses a type of experimental research with a pre-experimental method with a one group pretest-posttest design. The object of this research is the project-based learning model and the effectiveness of its application on student learning outcomes in the subject of electrical lighting installation. The subject of this research was class XII TITL SMK Muhammadiyah 1 Padang. The instruments used in this research were tests and student questionnaires. Based on the average posttest and questionnaire scores it is in the high category. Therefore, the application of the project-based learning model in the Electrical Lighting Installation subject is said to be effective because the percentage of student attitudes is quite high, the classical completeness score and effect size are included in the large category.